(untitled) (Journal of Information Technologies in Education (ITE), 2009)
It is shown results of connection of universities and scientific institutions to URAN network including optic fibers deployment in Ukrainian cities and URAN-GEANT 10 Gbps. It is discussed also means of providing of uninterruptable service to metropolitan area network users and implementation of network applied services.